2024
DOI: 10.1002/jemt.24488
|View full text |Cite
|
Sign up to set email alerts
|

Light and electron microscopic observations on retinal neurons of red‐tail shark (Epalzeorhynchos bicolor H. M. Smith, 1931)

Doaa M. Mokhtar,
Alessio Alesci,
Simona Pergolizzi
et al.

Abstract: The structure of photoreceptors (PR) and the arrangement of neurons in the retina of red‐tail shark were investigated using light and electron microscopy. The PR showed a mosaic arrangement and included double cones, single cones (SC), and single rods. Most cones occur as SC. The ratio between the number of cones and rods was 3:1.39 (±0.29). The rods were tall that reached the pigmented epithelium. The outer plexiform layer (OPL) showed a complex synaptic connection between the horizontal and photoreceptor ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(32 reference statements)
1
0
0
Order By: Relevance
“…Moreover, our histochemical analysis indicated that the IPL and OPL of the retina showed positive reactions for alcian blue. These results agree with the findings in frogs [ 65 , 66 ] and red-tail sharks [ 65 , 66 ], where this staining reaction indicates that the dye has bound to sulfate groups that are found in intracellular proteoglycans associated with membranes, such as those present in synaptic vesicles. These groups may serve as Ca 2 binding sites or preserve other ionic equilibriums.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, our histochemical analysis indicated that the IPL and OPL of the retina showed positive reactions for alcian blue. These results agree with the findings in frogs [ 65 , 66 ] and red-tail sharks [ 65 , 66 ], where this staining reaction indicates that the dye has bound to sulfate groups that are found in intracellular proteoglycans associated with membranes, such as those present in synaptic vesicles. These groups may serve as Ca 2 binding sites or preserve other ionic equilibriums.…”
Section: Discussionsupporting
confidence: 91%